Leadership Types in Support of Creativity and Innovation Within Video Game Studios in Indonesia - Loeis, Minaldi; Hubeis, Musa; Suroso, Arif Imam; Dirdjosaputro, Sukiswo (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study explores the leadership type most impacting organizational climate, creativity, and innovation in game studios. This study also addresses a gap in previous studies: organizational creativity's role in producing innovative products. This quantitative study of 68 respondents consisting of managers/owners and employees of game studios in Indonesia analyzes the type of leadership that affects organizational climate, creativity, and, ultimately, corporate innovation using an electronic survey during the COVID-19 pandemic. The respondents were acquired by invitations dispersed with the help of managing members of Asosiasi Game Indonesia and game developer social networks. The survey results were analyzed using the structural equation modeling partial least squares technique (PLS-SEM) using SmartPLS 3 software. This study shows that transformational leadership is the dominant leadership type and positively impacts a supportive organizational climate; such a climate also impacts organizational creativity. Transformational leadership also affects the kind of innovation in game studios. Understanding the factors of producing creative and innovative products in creative teams should improve the growth of video game producers. Keywords: creative industry, indonesia, leadership style, organizational innovation, video game development